1989
DOI: 10.1113/jphysiol.1989.sp017811
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of active sympathetic vasodilatation in the skin of the human foot.

Abstract: SUMMARY1. During operative aorto-femoral vascular reconstructions on sixteen patients, the sympathetic chain was stimulated electrically between the L2 and L4 ganglia while blood flow was monitored by laser doppler flowmeters from the skin on the sole of the foot and the ankle and by an electromagnetic flowmeter from the deep femoral artery. Epidural anaesthesia to at least the T6 level was used which excluded reflex effects.2. Stimulation (10 Hz) at 1-12 mA current strengths for 30 s evoked both reductions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Changed vascular response to sympathetic nerve stimulation was not limited to inflamed condition: Lundberg et al reported that the electrical stimulation of the sympathetic nerve caused cutaneous vasodilatation in patients with obstructive vascular disease [29]. We also measured BF in rats with chronic constriction injury using the same methods as in the present experiment, and found a BF-increase response to SS similar to that in AI rats (data not shown).…”
Section: Discussionsupporting
confidence: 56%
“…Changed vascular response to sympathetic nerve stimulation was not limited to inflamed condition: Lundberg et al reported that the electrical stimulation of the sympathetic nerve caused cutaneous vasodilatation in patients with obstructive vascular disease [29]. We also measured BF in rats with chronic constriction injury using the same methods as in the present experiment, and found a BF-increase response to SS similar to that in AI rats (data not shown).…”
Section: Discussionsupporting
confidence: 56%
“…The phenomenon reported by Allwood et al (1959) and Elam & Wallin (1987), that subjects with a low baseline blood flow tend to vasodilate, whereas those with a high baseline flow tend to vasoconstrict, in response to mental stress, is analogous to our finding that simultaneous stimulation of vasoconstrictor and vasodilator fibres induces vasodilatation at a low BRCF, but vasoconstriction at a high BRCF (Fig. 4), with the proviso that sympathetic rather than parasympathetic vasodilator fibres supply the skin of the limbs (Lundberg et al 1989). Oberle et al (1988) also reported that cold subjects, in whom the skin temperature was less than 25°C, responded to intraneural electrical stimulation of the median nerve, to mental stress or arousing stimuli, and to deep breaths with cutaneous vasodilatation, whereas the same stimuli given to warm subjects, with a skin temperature of more than 30°C, usually evoked cutaneous vasoconstriction.…”
Section: Sympathetic Nerve Stimulationsupporting
confidence: 65%
“…Another clinical study, which helps validate this proposed mechanism, was offered by Lundberg et al( 22). During aorto‐femoral reconstruction, 16 patients were electrically stimulated along their sympathetic chain from L2‐L4 ganglia.…”
Section: Discussionmentioning
confidence: 85%